Effect of miss-distance on the airfoil-vortex interaction. Experiment - Selerowicz, W.; Sobieraj, G.; Szumowski, A.; Piechna, J. (Archives of Mechanics, 1998)
The effect of a strong vortex interacting with an airfoil flow is investigated experimentally by means of a shock tube. The experiments follow the previous theoretical work [11] on this subject. The instantaneous pressure distributions and histories of lift coefficient during the vortex passage are presented. The flow is visualised using the schlieren method. It is found that due to the viscosity of the air not taken into account in numerical study, the effect of miss-distance in the range of up to 0.5 chord length is weaker than it was initially predicted.